‘Predatory’ Open Access Journals as Parody: Exposing the Limitations of ‘Legitimate’ Academic Publishing - Kirsten Bell (tripleC: Communication, Capitalism & Critique)
The concept of the ‘predatory’ publisher has today become a standard way of characterizing a new breed of open access journals that seem to be more concerned with making a profit than disseminating academic knowledge. This essay presents an alternative view of such publishers, arguing that if we treat them as parody instead of predator, a far more nuanced reading emerges. Viewed in this light, such journals destabilize the prevailing discourse on what constitutes a ‘legitimate’ journal, and, indeed, the nature of scholarly knowledge production itself. Instead of condemning them outright, their growth should therefore encourage us to ask difficult but necessary questions about the commercial context of knowledge production, prevailing conceptions of quality and value, and the ways in which they privilege scholarship from the ‘centre’ and exclude that from the ‘periphery’.